2022
DOI: 10.3389/fanim.2022.914772
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Dried Neem Leaf Extract on the Growth Performance, Meat Yield and Meat Quality in Skeletal Muscle of Broiler Chickens Under High-Temperature Conditions

Abstract: We aimed to examine the effects of cyclical high ambient temperature (HT) and dried Neem (Azadirachta indica) leaf extract (DNE) supplementation on the growth performance, muscle lipid peroxidation level, and muscle drip loss of broiler chickens. Twenty-four 15-day old broiler chickens (Chunky strain ROSS 308) were divided into four treatment groups that were fed diets with or without 2.0% DNE under thermoneutral (25 ± 1°C) or cyclical HT (35 ± 1°C for 8 h/day) conditions. Supplementation of DNE did not affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…Antioxidant activities of neem leaves from India (Wandscheer et al, 2004), England (Salehzadeh et al, 2003), Nepal (Ghimeray et al, 2009, Brasil (Nagano and Batalini 2021), Thailand (Sithisarn et al, 2006), Nigeria (Olaitan et al, 2021 have also been reported. Neem leaves and oil were reported maximum antioxidant activity % because of its phenolic compounds and enormous scavenger ability towards free radical (Nikolova et al, 2022;Nakamura et al, 2022). These observations are a close agreement to the current study.…”
Section: Fig2 H 2 O 2 Scavenging Activity (%) Of Azadirachta Indicasupporting
confidence: 93%
“…Antioxidant activities of neem leaves from India (Wandscheer et al, 2004), England (Salehzadeh et al, 2003), Nepal (Ghimeray et al, 2009, Brasil (Nagano and Batalini 2021), Thailand (Sithisarn et al, 2006), Nigeria (Olaitan et al, 2021 have also been reported. Neem leaves and oil were reported maximum antioxidant activity % because of its phenolic compounds and enormous scavenger ability towards free radical (Nikolova et al, 2022;Nakamura et al, 2022). These observations are a close agreement to the current study.…”
Section: Fig2 H 2 O 2 Scavenging Activity (%) Of Azadirachta Indicasupporting
confidence: 93%